Policing for Peace in Northern Ireland - Murphy, J. author. aut Link
XII, 239 p.
Keywords: This is the first in-depth analysis of the transition from the RUC to the PSNI seen through the eyes of key figures, inside and outside the organization. It provides a fresh insight into the wider social and political context in which this change occurred and is a significant contribution to the story of the Northern Ireland peace process.